Investigação das bases moleculares do câncer não medular familiar da tireoide - Lima, Erika Urbano de [UNIFESP] (2018)
Almost 95% of thyroid cancer cases originate from follicular thyroid cells (NMTC). The majority are sporadic (90%), but 3-9% correspond to familial forms (FNMTC) characterized by three or more first-degree relatives affected by thyroid cancer. It can be divided into different subgroups: familial papillary thyroid carcinoma (PTC) with or without oxyphilia cell, familial PTC with papillary renal cell carcinoma, and familial PTC with multinodular goiter. Some chromosomal loci and genes were associated with CNMFT in families with specific phenotypes. It has been proposed that FNMTC may be a polygenic disease with autosomal dominant inheritance with variable penetrance. The objective of this study was to identify genetic variants involved in the susceptibility to FNMTC in two Brazilian families using Whole Exome Sequencing (WES) and specific bioinformatics analyses. WES of DNA samples from peripheral blood leukocyte was performed using SureSelectXT Human All Exon V6+UTR Capture Library kit (Agilent) and the Illumina® NextSeq ™ 500 platform. For the variants selection an extensive bioinformatics analysis was performed using 12 specific programs and 4 population databases (ExAc, AbraOM, dbSNP and Ensembl). In the first family from Manaus (Amazonas) and characterized as familial PTC with multinodular goiter, the c.C110A variant of the ACTL8 gene was exclusively present in all affected individuals. The analysis showed that the ACTL8 variant may impair the protein function and structure, and that this protein could interact with the cytoskeleton and epithelial differentiation proteins. The c.C623T and c.C2654T variants of the SRPX2 and EPHB1 genes were identified in the second family from Jacobina (Bahia) classified as familial PTC without oxyphilic cells. Both variants were classified as damaging in all prediction analyzes and the joint presence of these variants showed increased odds ratio to develop the disease (OR= 51; 95% CI: 1.7046 - 1525.9024; P=0.0234), with 100% of sensitivity and 88.9% of specificity. It was also was observed that both proteins (SRPX2 and EPHB1) would participate in a network of protein interactions related to MAPK pathway activation.These results suggest that the ACTL8, SRPX2 and EPBH1 genes variants identified in this study confer susceptibility to the development of FNMTC in these particular families. These results are in agreement with the literature that suggests that the genetic factors of FNMTC susceptibility are specific to each family.